Goal setting practice in chronic low back pain. What is current practice and is it affected by beliefs and attitudes?. (3rd October 2018) - Gardner, Tania; Refshauge, Kathryn; McAuley, James; Hübscher, Markus; Goodall, Stephen; Smith, Lorraine
ABSTRACT: Introduction : Goal setting, led by the patient, is promising as an effective treatment for the management of chronic low back pain (CLBP); however, little is known about current practice. The aims of the study were to explore (1) current goal setting practice in CLBP among physiotherapists; (2) perceived barriers to goal setting in CLBP; and (3) relationship between clinician's attitudes and beliefs and goal setting practice.Method : A cross-sectional observational survey.Results : The majority of respondents used goal setting with the main aim of facilitating self-management. The greatest number of goals were set with 50% therapist/50% patient involvement. The most common perceived barriers to goal setting related to time constraints and lack of skill and confidence. A higher biomedical score for treatment orientation of the therapist was associated with a lower patient involvement score.Conclusion : Goal setting is common practice for CLBP and is perceived as a high priority. It is more often a collaboration between therapist and patient rather than patient-led with treatment orientation of the physiotherapist a predictor of patient involvement. Education of healthcare professionals needs to include better understanding of chronic pain to orient them away from a biomedical treatment approach, as well as to enhance skills in facilitating patient involvement in goal setting.